Diagnostic evaluations and management of surgical scar endometriosis: a case series of 13 cases over 9 years - Kanakaraya, Jamuna; Kanakaraya, S.; Chandrahasa; Bhardwaj, Avni (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Endometriosis is defined as localization of ectopic functional endometrial gland and stroma. Scar endometriosis is a rare benign gynecological disease affecting women in the reproductive age group. It’s incidence in post-caesarean and post-hysterotomy scar tissue is approximately 0.03-0.4% and 1.08-2% respectively. This case series reviews literature of medical data of 13 patients who presented over 9 years with incisional site endometrioma, diagnostic approaches and treatment is discussed. The patients presented in 2nd to 3rd decade of life with complaints of cyclical pain and mass at previous surgery scar. Ultrasonography (USG) detected hypoechoic mass/granuloma and inconclusive in most cases. Magnetic resonance imaging (MRI) though was suggestive of diagnosis in almost all cases. Definitive diagnosis was histopathological examination. Treatment was achieved with surgical excision in all patients, and 3 are preceded by hormonal treatment. Medical treatment can only yield symptomatic relief in pain till the hormone effect lasts. Treatment of choice is wide excision that is excision of 1 cm tissue around the mass. Endometriosis in operative site scar tissue may present as a discrete mass which may be painful and can be confused clinically with a variety of surgical conditions. It is extremely important to recognize the condition so as to avoid potential clinical pitfalls in the diagnosis of this treatable entity.